La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Ideología argentina (Universidad Nacional de Quilmes), 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; lit3220; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppressions; thématiques; théologie; voiles islamiques

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty--and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Histoire des femmes en Occident - Duby, Georges; Perrot, Michelle (Plon, 1991)
Projet démesuré que de couvrir près de vingt siècles d'histoire du monde antique gréco-romain, de parcourir un espace qui va des rivages de la Méditerranée à ceux des mers du Nord, des colonnes d'Héraklès aux rives de l'Indus, de se plonger dans des documents aussi divers que les tombes d'une nécropole, la stèle inscrite plaquée aux murs du sanctuaire, le rouleau de papyrus, la scène peinte sur la panse d'un vase... et une littérature grecque et latine qui, si elle n'a pas donné la parole aux femmes, a beaucoup parlé d'elles. On l'aura deviné, ce livre n'a pas pour fonction de remplacer l'énorme production qui existe en ce domaine. Il aborde un petit nombre seulement des questions qui nous ont paru importantes pour aider à comprendre la place des femmes dans le monde antique et, plus encore peut-être, dans la perspective d'un ensemble de volumes traitant de l'histoire des femmes, comprendre les fondements d'habitudes mentales, de mesures juridiques, d'institutions sociales qui ont duré des siècles en Occident.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; antiquité; approches et analyses; conditions des femmes*; cours; discipline; europe; his4330; histoire; histoire des femmes*; histoire et politique; incontournable; lit3220; moyen-âge; occident; oui; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

L'amour sous Victoria : sexualité et classes populaires à Londres au XIXe siècle - Barret-Ducrocq, Françoise (Plon, 1989)
Keywords: 1800-1899; amour; approches et analyses; classe ouvrière; cours; discipline; discours dominant; europe; his4860; histoire; histoire de la sexualité; histoire et politique; inégalités; londres; premier cycle; périodes historiques; rapports sociaux de sexe; royaume-uni; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; époque victorienne

Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture, 1989)
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Cheap amusements: Working women and leisure in turn-of-the-century New York - Peiss, Kathy Lee (Temple University Press, 1986)
Contenu: The Homosocial World of Working-Class Amusements -- Leisure and Labor -- Putting on Style -- Dance Madness -- The Coney Island Excursion -- Cheap Theater and the Nickel Dumps -- Reforming Working Women's Recreation.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; his4443; histoire; histoire des femmes*; histoire et politique; loisirs des femmes*; new york; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail; travail des femmes*

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Studies on the history of Quebec, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Femme, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Histoire du feminisme français : du moyen âge à nos jours - Albistur, Maite; Armogathe, Daniel (Des femmes, 1977)
« Il s’agit de faire toute la lumière possible, en l’état actuel des connaissances, sur une protestation aussi ancienne que la pensée, mais régulièrement déjouée par les pièges de l’imaginaire masculin et du discours dominant. » Cette « querelle » des femmes a été analysée selon quatre temps forts : le temps du féminisme élitaire (du VIe siècle à 1789) ; une période de féminisme en mouvement (1789-1871) ; un temps de féminisme bourgeois et réformiste (1871-1945) ; enfin, une période de féminisme radical, inaugurée par Simone de Beauvoir dans Le Deuxième Sexe (1949). « C’est au total quinze siècles d’une autre histoire qui se déroulent sous nos yeux dans ces 500 pages d’analyse patiente, une histoire tour à tour sereine et passionnée, grave et légère, besogneuse et festive, une histoire arrachée aux pesanteurs des mythes, des doutes et de la mauvaise foi. » M.A. et D.A.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; approches et analyses; conditions des femmes*; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire du féminisme; histoire et politique; lit3220; moyen-âge; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Histoire de la sexualité I. La volonté de savoir - Foucault, Michel (Bibliothèque des histoires, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; his4860; histoire; histoire de la sexualité; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques

L’hypothèse répressive - Foucault, Michel (Histoire de la sexualité. 1. La volonté de savoir, 1976)
"L'Histoire de la sexualité, articulée en trois volumes (La volonté de savoir, L'usage des plaisirs et Le souci de soi), prolonge les recherches entreprises avec L'archéologie du savoir et Surveiller et punir. Michel Foucault concentre ses analyses sur la constellation de phénomènes que nous désignons par le « sexe » et la sexualité. L'axe de cette entreprise n'est pas de s'ériger contre une « répression » de la sexualité afin de la « libérer », mais de montrer comment la vie sexuelle a enclenché une volonté systématique de tout savoir sur le sexe qui s'est systématisée en une « science de la sexualité », laquelle, à son tour, ouvre la voie à une administration de la vie sexuelle sociale, de plus en plus présente dans notre existence.Foucault fait ainsi l'archéologie des discours sur la sexualité (littérature érotique, pratique de la confession, médecine, anthropologie, psychanalyse, théorie politique, droit, etc.) depuis le XVIIIe siècle et, surtout, au XIXe, dont nous héritons jusque dans les postures récentes de « libération sexuelle ». L'attitude de censure et celle d'affranchissement se rencontrent finalement dans le même type de présupposé : le sexe serait cause de tous les phénomènes de notre vie comme il commanderait l'ensemble de l'existence sociale."-- Site de l'éditeur.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; analyse de discours; approches et analyses; cours; discipline; discours dominant; foucault; histoire; occident; philosophie; post-structuralisme; postmodernisme; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex1183; sexe; sexualité; systèmes d'oppressions; thématiques